Genetic diversity of Colletotrichum gloeosporioides species complex associated with Citrus wither‐tip of twigs in Tunisia using microsatellite markers. Issue 6 (21st April 2019) - Bahri, Bochra Amina; Saadani, Mariem; Mechichi, Ghaya; Rouissi, Wafa
Abstract: Anthracnose Citrus disease has been associated with several symptoms worldwide and it is recently compromising Citrus production in the Mediterranean area. Four species complexes are mainly involved: Colletotrichum boninense, C. acutatum, C. gloeosporioides and C. truncatum . In this study, we investigated the genetic diversity of Colletotrichum spp. in Tunisia associated with wither‐tip of twigs on Citrus . Specific primers ITS4‐CgInt allowed the identification of C . gloeosporioides species complex in all the 54 isolates, sampled from three regions and four Citrus species. Overall, our genotypic analysis using 10 SSR markers showed a moderate diversity level in Tunisian C. gloeosporioides population and highlighted that C. gloeosporioides reproduce mainly clonally. In addition, heterothallic isolates were present in our population, suggesting that the pathogen population may undergo parasexual recombinations. The highest genetic diversity in C. gloeosporioides was recorded in Nabeul and on orange, which likely constitutes the area and the host of origin for the Citrus anthracnose disease in Tunisia. In addition, no population subdivision was detected at the geographic, host species or cultivars' origin levels. However, our study identified two genetic subpopulations and indicated a rapid C. gloeosporioides population change at temporal scale that should be further examined over several consecutive growing seasons in order to understand its population dynamics.